History for comprehensive schools - Tan, M. H. (Kuala Lumpur : Shanghai Book Company Ltd., 1964)
PREFACE The aim of this series is to interest the Secondary pupil in the story of his own country and to tell something also of the story of the world in which he lives. It is based on the Syllabus for the Lower Secondary Schools. It is simply written and well illustrated. At the same time, the writer tries also to convey to the pupil two fundamental concepts in History i.e. Time and Space. For this reason the time charts and the maps form an integral part of the contents and exercises in this series. The Third Book deals with contemporary events which are not only complex but also numerous. How to reduce this mass of events into a coherent and yet reasonably short account is quite a problem. However, the writer hopes her treatment here has made this problem less difficult for the history teachers in the secondary schools. Once again, though it may appear redundant already, the writer wishes to thank all those who have made the publication of this series possible.
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: History, Modern -- Study and teaching (Secondary)